2012
DOI: 10.1016/j.limno.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Do macrophytes, diatoms and non-diatom benthic algae give redundant information? Results from a case study in Poland

Abstract: a b s t r a c tWe analyzed species composition and abundance of macrophytes, diatoms and non-diatom benthic algae, water chemistry and habitat structure of 24 river sites in Poland, in order to better understand which parameters structure macrophyte and benthic algae communities. Community patterns for macrophytes and diatoms are most closely related, while macrophytes and non-diatom benthic algae have the weakest relationship. Environmental parameters best explaining community patterns are channel substrate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 33 publications
4
28
0
1
Order By: Relevance
“…The search for an explanation of observed patterns in diversity-productivity relationships in meta-analysis (Whittaker, 2010;Cardinale et al, 2011) might therefore be complicated by the fact that some studies deal exclusively with diatoms, whilst others pool diatoms and non-diatom benthic algae richness. Our results are consistent with the results of Schneider et al (2012), who described differences in stream diatom and non-diatom benthic algae community patterns, and suggest that benthic primary producers in streams are not the homogenous group they often are treated as. Moreover, whilst diatom and non-diatom indices both are suitable for status assessment, their assemblage patterns follow different ecological principles.…”
Section: Consequences Of the Different Richness Patternssupporting
confidence: 92%
See 1 more Smart Citation
“…The search for an explanation of observed patterns in diversity-productivity relationships in meta-analysis (Whittaker, 2010;Cardinale et al, 2011) might therefore be complicated by the fact that some studies deal exclusively with diatoms, whilst others pool diatoms and non-diatom benthic algae richness. Our results are consistent with the results of Schneider et al (2012), who described differences in stream diatom and non-diatom benthic algae community patterns, and suggest that benthic primary producers in streams are not the homogenous group they often are treated as. Moreover, whilst diatom and non-diatom indices both are suitable for status assessment, their assemblage patterns follow different ecological principles.…”
Section: Consequences Of the Different Richness Patternssupporting
confidence: 92%
“…Though most use diatoms as proxies for the complete phytobenthos assemblage, the validity of this approach has been questioned (Schneider et al, 2012). Indices based on speciescomposition of non-diatom benthic algae have been developed for trophic status (periphyton index of trophic status PIT, Schneider & Lindstrøm, 2011) and acid conditions (acidification index periphyton AIP, Schneider & Lindstrøm, 2009) for rivers in Norway.…”
Section: Introductionmentioning
confidence: 99%
“…Indices derived from macrophytes might not be a direct indication of water-column nutrient concentrations because most macrophytes derive most of their nutrients from the sediments, whereas their epiphytes rely on nutrients in the littoral water column and are considered the primary scavengers of nutrients from the water column (Wetzel 2001). The shorter generation time for diatoms means they provide an indication of increasing or decreasing water quality over time scales of weeks, whereas macrophytes, with longer generation times and lower rates of dispersal, are slower to respond (Schneider et al 2012). Schneider et al (2012) suggested that differences in assessments between biotic indices based on diatoms and those based on macrophytes are expected in ecosystems subjected to environmental change, and they postulated that differences between indices inform us of ecosystem stability.…”
Section: Model Performancementioning
confidence: 99%
“…The shorter generation time for diatoms means they provide an indication of increasing or decreasing water quality over time scales of weeks, whereas macrophytes, with longer generation times and lower rates of dispersal, are slower to respond (Schneider et al 2012). Schneider et al (2012) suggested that differences in assessments between biotic indices based on diatoms and those based on macrophytes are expected in ecosystems subjected to environmental change, and they postulated that differences between indices inform us of ecosystem stability. In some lakes, we recorded either no difference (Wastwater, (Table 5).…”
Section: Model Performancementioning
confidence: 99%
“…According to the WFD, macrophytes and phytobenthos comprise one biological quality element. The applicability of different plant groups can be more or less restricted due to the spatial scale and their behaviour is influenced by the stability or changes of river environmental conditions (Schneider et al, 2012).…”
Section: Introductionmentioning
confidence: 99%